Provision of food at Casa del Buen Pastor Women’s Prison (Legal journal - Research in Legal and Social Sciences, 2023)
This paper aims to analyze the processes of food provision to inmates in the country’s penitentiaries, focusing on the “Casa del Buen Pastor” Women’s Penitentiary in Asunción, including the intervention of different organizations, both from the public and private sectors in these processes. For this purpose, a qualitative research has been carried out, through the review of national and international documents, regulations that the Paraguayan State is obliged to comply with. On the other hand, research and semi-structured interviews were conducted, as well as data collection and analysis of the bidding processes of the last few years. This paper begins with the assumption that the shortage, disproportion and absence of food, in some cases due exclusively to corruption within the prison, and that these in turn have a direct and negative impact on the general nutrition of imprisoned women. In this understanding, the findings allowed to broaden the perspective and awareness of the complexity of the issue, considering that there are several aspects that influence the adequate provision of food, in proportion, quality, and nutritional content according to the needs of the prison population.
Keywords: Corruption; food security; imprisonment; Casa del Buen Pastor